From centrally planned culture to entrepreneurial culture: The example of Bulgarian and Romanian organisations - Mihaela Kelemen; Latchezar Hristov (Journal for East European Management Studies, 1998)
The dismantling of the socialist mode of production in Bulgaria and Romania has marked the beginning of a turbulent and unprecedented period which poses new challenges to organisations. While in the past organisations were mere extensions of the five year central plan, they now have to take responsibility for their actions in the market place. In addition, the loss of the COMECON market has exposed organisations to international competition and the need to explore global opportunities. The paper presents eight organisations which have established themselves as quality suppliers for the Western market by managing successfully the change from centrally planned culture to entrepreneurial culture. – – Nach der Aufgabe der sozialistischen Produktionsweise in Bulgarien und Rumänien sahen sich Unternehmen plötzlich grundsätzlich neuen Herausforderungen gegenüber. In der Vergangenheit war die Planung in Organisationen eine einfache Funktion des Fünf-Jahres-Plans. Heute trägt das Management die Verantwortung für seine Entscheidungen. Der Verlust des COMECONMarktes bedeutete außerdem mehr internationalen Wettbewerb und den Zwang, global aktiv zu werden. In diesem Aufsatz werden acht Firmen vorgestellt, die es geschafft haben, sich als Zulieferfirmen für den westlichen Markt zu etablieren und damit die Veränderung von einer planwirtschaftlichen zu einer Kultur des Unternehmertums vollzogen haben.
Keywords: 650